2004
DOI: 10.1007/s00228-004-0810-8
|View full text |Cite
|
Sign up to set email alerts
|

Are we going to increase the use of antidepressants up to that of benzodiazepines?

Abstract: In Italy, the consumption of benzodiazepines was not affected by the increased prescribing of selective serotonin-reuptake inhibitors and newer antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 15 publications
0
40
0
1
Order By: Relevance
“…In an earlier national Italian study (1992)(1993), the prevalence of benzodiazepine use was found to be 8.6% in 1993 and doses to be 49.4 DDD/1,000 inhabitants/day in 1991; 28 benzodiazepines were available (60 brands and 133 products) [35] . Another Italian national study found benzodiazepine use to be stable with 50 DDD/1,000 inhabitants/day from 1995 to 2003 as compared to the marked increase in DDDs for SSRI antidepressants [36] . In Switzerland ( table 4 ) with 17 different benzodiazepines available in 2002, 43.3 DDD/1,000 inhabitants/day are reported with a 6-month prevalence of 9.1% [37] .…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier national Italian study (1992)(1993), the prevalence of benzodiazepine use was found to be 8.6% in 1993 and doses to be 49.4 DDD/1,000 inhabitants/day in 1991; 28 benzodiazepines were available (60 brands and 133 products) [35] . Another Italian national study found benzodiazepine use to be stable with 50 DDD/1,000 inhabitants/day from 1995 to 2003 as compared to the marked increase in DDDs for SSRI antidepressants [36] . In Switzerland ( table 4 ) with 17 different benzodiazepines available in 2002, 43.3 DDD/1,000 inhabitants/day are reported with a 6-month prevalence of 9.1% [37] .…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies conducted in Chile, Italy and Spain have revealed prevalence of use of between 4 and 7.5% over the past 12 months. [3][4][5] A fi gure of 10.2% has been found for the city of SĂŁo Paulo, Brazil. 6 A higher rate of 21.3% has been found in Porto Alegre, in southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Venlafaxine is capable of inhibiting central serotonin and norepinephrine neuronal reuptake, and has increasingly been used in the treatment of depression and anxiety disorder (Holliday and Benfield, 1995;Ciuna et al, 2004). It is associated with a number of predictable adverse effects that are generally mild, including tachycardia, increased blood pressure, fatigue, headache, dizziness, sexual dysfunction, and dry mouth (Johnson et al, 2006;Stahl et al, 2005).…”
Section: Introductionmentioning
confidence: 99%